Fluktuasi Mekanisme Pasar Harga Sawit dan Kemampuan Petani Bertahan dalam Pengelolaan Menurut Konsep Mabi’ - Khairul Ambiya (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
The marketing of oil palm Fresh Fruit Bunches is a process of commodity flow which includes the transfer of property rights and the creation of time, place, and form. However, lately fluctuations in palm oil prices, especially in Fresh Fruit Bunches, have made farmers waver in the cultivation of this plantation business. This condition of course directly affects the performance of farmers, for that the development of the oil palm plantation sector needs to be accompanied by a good price structure to stimulate the performance of plantation business actors, because the price of plantation commodities is a determinant for farmers to engage in oil palm plantation business. This paper is a qualitative research using literature as a research approach. This study aims to determine price fluctuations, market mechanisms, and the concept of mabi'. The reality of palm oil prices in farmers' local markets does not always benefit. This is because farmers cannot determine the selling value of agricultural products, in certain circumstances farmers experience losses from their crops due to falling selling value factors, so it is not comparable to the maintenance costs and operational costs incurred by farmers. This matter in the concept of buying and selling recommended by Islam (mabi') burdens one party, because the determination of prices is not carried out by the seller or buyer directly, but determined by a third party.